PENYULUHAN PENDAMPINGAN ORANG TUA DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT ANAK DI KOMUNITAS SERPONG, BANTEN - Carolina Marpaung; Rahmi Amtha; Armelia Widyarman; Enrita Rahmadini; Florencia Livia (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
An online training activity was carried out regarding the assistance of parents in maintaining the dental and oral health of pre-school age children living in the Serpong area, South Tangerang, Banten. This training was designed considering the high caries rate of Indonesian children over the last 10 years. Given the importance of developing good health behavior from an early age, the intake of non-cariogenic foods and oral hygiene maintenance habits should also be carried out as early as possible. The role of parents is vital in teaching and supervising pre-school age children’s behavior. Therefore, this training was conducted to increase parental participation in supervising children's eating patterns and cleaning the oral cavity. This should be followed by correction of diet and better oral hygiene habits to reduce children’s caries rate. Early assessments show most parents still have a wrong understanding of caries prevention in children, especially in children who still receive breast milk. The final assessment demonstrates an improved understanding in the etiology of oral diseases and parental assistance in dental and oral health maintenance in children.